Conception of Local Wisdom Nangun Sad Kerthi Loka Bali In Character Education - Putu Ronny Angga Mahendra (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
Local wisdom is a wealth that can be used as a philosophy of learning in life that is in accordance with the way of life of the local community. One of the local wisdoms in Bali that supports and can be utilized in this case is Nangun Sad Kerthi Loka Bali, as an alternative to the current government to provide character education based on local wisdom. As one of the things set forth as the vision and mission of the Governor of Bali in carrying out the development of Balinese society. Development does not only include physical and non-physical aspects, in this case the quality of the Balinese people themselves. The characters that can be formed from government programs in the vision of Nangun Sad Kerthi Loka Bali are the spirit of nationality, love for the country, caring for the environment, caring socially, and responsibility. This will be a provision to keep abreast of global progress and still strengthen local wisdom as one's identity.